Revisiting the Natural History of Chronic Hepatitis B in Asian Americans - Pan, MD, Calvin; Chiang, MD, Betty (North American Journal of Medicine and Science, 2009)
Worldwide, there are estimated to be 400 million people chronically infected with hepatitis B virus (HBV). In Asia, perinatal transmission of HBV from mother to newborn accounts for the high incidence of CHB infection Perinatally acquired CHB patients have unique features in their natural history, characterized by a long duration of immunotolerance phase, unpredictable patterns of disease reactivation and inactivation, and high risk for cirrhosis or HCC. Asian Americans, 60% of whom are foreign born, thus have similar patterns in the natural history of their disease. This article is a systemic review on the natural history of CHB in the Asian and Asian American population. Future research directions in this special population will also be explored.